Increasing the Batch Size of a QESD Crystallization by Using a MSMPR Crystallizer - Jerome Hansen; Peter Kleinebudde (MDPI AG, 2022)
Quasi-emulsion solvent diffusion (QESD) crystallizations can improve the micromeritic properties of drugs and excipients. A solution is dispersed in a miscible antisolvent as a transient emulsion. Using this technique, substances that normally crystallize in the form of e.g., needles, agglomerate into spherical, hollow particles. A disadvantage of QESD crystallizations is that the particle size of the agglomerates decreases with an increased solvent fraction of the mother liquor. Therefore, in batch production, many consecutive runs have to be performed, which is a time- and material-intensive process. The aim of this study was to convert a previously used lab-scale batch crystallizer into a mixed-suspension, mixed-product removal (MSMPR) crystallizer, since the batch size could be simply increased by increasing the run time of the system. The mean residence time (MRT) and solvent fraction in the system was predicted and verified using actual measurement curves. The experiments showed that >50 g QESD metformin hydrochloride could be crystallized in a single run, without observing a large shift in the particle size, while maintaining good flowability. Observations regarding the effect of the MRT on the particle size distribution could be verified for the production on a larger scale than previously described.